Árvay Emléknap 2017. május 26. - Póka, Róbert (Gerundium, 2019)
Árvay Memorial Day. The Department of Obstetrics and Gynaecology of the University of Debrecen organised a memorial meeting in honour of its former director, Professor Sándor Árvay, on the occasion of the 20th anniversary of his death. The text presents the events of the memorial day (the inauguration of the statue of Professor Árvay, a memorial scientific sitting, a meeting of the retired colleagues), the major events of Professor Árvay’s life and his merits.